Faktor-Faktor yang Berhubungan dengan Perilaku Seksual Pranikah Pada Remaja di SMA X Kecamatan Lempuing OKI Tahun 2021 - Ika Fitri Mueliana; Siti Aisyah; Merisa Riski (Universitas Batanghari Jambi, 2022)
Premarital sexual behavior is behavior related to sexual urges with the opposite sex or same sex that is carried out before the existence of a legal marriage bond. WHO states that in developing countries 21 million adolescent girls aged 15-19 years experience pregnancy each year and 49% of pregnancies are unwanted. The IDHS (2017) states that adolescents aged 15-24 years holding hands: Women 64% Men 75%, Kissing lips: Women 30% Men 50%, Hugging: Women 17% Men 33%, likes 82% and loves each other 83% . In Palembang City, 456 teenagers became pregnant out of wedlock and 159 gave birth to health workers. In SMA X Lemrub the results of interviews with 10 students have been in a relationship and sent romantic words, 6 teenagers have walked hand in hand, 2 have hugged, kissed. The purpose of this study was to determine the relationship between parenting, smartphone use, and socioeconomic with premarital sexual behavior in adolescents. This type of research is quantitative with an analytical survey method with a cross sectional approach. The population in this study were 515 students in class X, XI and XII with 84 samples taken by random sampling. Primary data were processed and analyzed by univariate and bivariate analysis and Chi-Square test. The results and conclusions found the relationship between parental parenting with Pvalue = 0.002, smartphone use Pvalue = 0.000 and socio-economic Pvalue = 0.050 with premarital sexual behavior in adolescents at SMA X Lemrub OKI. It is hoped that the results of this study can be used as input for making effective school regulations for adolescents to prevent premarital sexual behavior in adolescents